2018
DOI: 10.1101/286500
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A mutation-independent approach via transcriptional upregulation of a disease modifier gene rescues muscular dystrophy in vivo

Abstract: Introductory paragraphIdentification of protective and/or pathogenic genetic modifiers provides important insight into the heterogeneity of disease presentations in individuals affected by neuromuscular disorders (NMDs), despite having well-defined pathogenic variants. Targeting modifier genes to improve disease phenotypes could be especially beneficial in cases where the causative genes are large, structurally complex and the mutations are heterogeneous. Here, we report a mutation-independent strategy to upre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…This construct was guided to the Lama1 proximal promoter region by a combination of three sgRNAs. We showed that systemic administration of AAV9-carrying the CRISPR/dCas9 components led to robust up-regulation of laminin-α1 in the dy 2j /dy 2j mice, resulting in the amelioration of dystrophic features in skeletal muscle and improvement in mobility and muscle functions of the mice [25].…”
Section: Crispr/dcas9-mediated Modulation Of a Compensatory Gene In Mmentioning
confidence: 95%
See 1 more Smart Citation
“…This construct was guided to the Lama1 proximal promoter region by a combination of three sgRNAs. We showed that systemic administration of AAV9-carrying the CRISPR/dCas9 components led to robust up-regulation of laminin-α1 in the dy 2j /dy 2j mice, resulting in the amelioration of dystrophic features in skeletal muscle and improvement in mobility and muscle functions of the mice [25].…”
Section: Crispr/dcas9-mediated Modulation Of a Compensatory Gene In Mmentioning
confidence: 95%
“…Concerns over the long-term safety of delivering genome-modifying cargo to cells and host immune responses to the AAV vectors and the cargo must also be addressed. In the case of MDC1A, amelioration of disease phenotypes in vivo highly depends on efficient targeting in both the skeletal muscles and peripheral nerves [21,25]. Improvements of the biodistribution, tissue penetration and, in particular, editing efficiency are required in order to fully exploit the potential of therapeutic AAV delivery.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Additionally, dCas9-VP160 was used in rag/mdx mice to upregulate the laminin subunit alpha 1 chain (Lama1) to increase laminin-111 to stabilize the muscle fiber membrane (102). For MDC1A, a non-mutation specific approach with SadCas9-2xVP64 was used to upregulate Lama1, which can compensate to rescue the dy 2J /dy 2J phenotype in vivo (59).…”
Section: Activation Of Genesmentioning
confidence: 99%
“…Using two vectors for one platform may effectively halve the effective dose. SaCas9 is an alternative, smaller nuclease that can be packaged along with a gRNA into a single AAV and has been successfully applied in some models of NMDs (15,36,59,60,97,98,104,110,122,131). However, a higher percentage of the population is estimated to have pre-existing immunity to SaCas9 compared with SpCas9 (23,119).…”
Section: Delivery Of Crisprmentioning
confidence: 99%
See 1 more Smart Citation